Primary School Students' Reaction to the Web as a Classroom Resource - Large, Andrew; Beheshti, Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Two grade-six classes in a Montreal primary school used the Web over several weeks to gather information for a class project. After the completion of the project, 50 students were interviewed to gather their opinions on this experience. They discuss the relative merits of the Web as compared with traditional printed sources in terms of information content and retrieval. Although the Web certainly had its enthusiasts, books and magazines also continued to be important. The students commented upon a number of problems they encountered in finding information suitable for their project. To become a more effective classroom tool, the authors conclude either that more helpful interfaces are required to assist in search formulation or that students must be taught how to seek information in this environment. In addition, more information is required on the Web that can be used by young students, and pathfinders are needed to point the students in the right direction.